2015
DOI: 10.1037/ort0000038
|View full text |Cite
|
Sign up to set email alerts
|

Childhood victimization, attachment, psychological distress, and substance use among women on probation and parole.

Abstract: The present analysis was guided by a gendered pathways-based theoretical model and examined relationships between childhood victimization and current attachment, psychological distress and substance use among 406 women with histories of victimization who were on probation and parole in an urban Kentucky county. Structural equation modeling examined relationships among childhood victimization, attachment, psychological distress, and substance use. Additionally, we examined the mediational role that attachment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 111 publications
(163 reference statements)
2
18
0
Order By: Relevance
“…Similarly, Dewitte, De Houwer, and Buysse () showed that attachment anxiety, and not avoidance, was related to lower implicit relational self‐esteem. Although adult attachment styles are stable over time (Dykas & Cassidy, ), negative (or traumatic) experiences may create an insecure attachment style in previously secured individuals (Winham et al, ). With this in mind, it has been suggested that therapeutic intervention may support anxiously attached or avoidantly attached individuals to improve attachment security (e.g., Kinley & Rayno, ; Marmarosh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dewitte, De Houwer, and Buysse () showed that attachment anxiety, and not avoidance, was related to lower implicit relational self‐esteem. Although adult attachment styles are stable over time (Dykas & Cassidy, ), negative (or traumatic) experiences may create an insecure attachment style in previously secured individuals (Winham et al, ). With this in mind, it has been suggested that therapeutic intervention may support anxiously attached or avoidantly attached individuals to improve attachment security (e.g., Kinley & Rayno, ; Marmarosh, ).…”
Section: Introductionmentioning
confidence: 99%
“…When the child does not receive the adequate response needed from the caregiver, insecure attachment styles are formed. Each child develops his own set of expectations, or internal working models, in regards to their caregivers' responsiveness and availability to their needs (Winham et al, 2015). These models are internalized by the child and develop into schemas for how the adult sees him-or herself and interpersonal relationships in the future (Winham et al, 2015).…”
Section: Attachment Theorymentioning
confidence: 99%
“…Researchers have reported that the consequences of maltreatment play a greater role in the development of delinquent behavior in females than in males (Foy, Ritchie, & Conway, 2012). In a recent study, Winham et al (2015) examined the role attachment plays between childhood victimization, psychological distress and substance misuse among 406 women on probation who have a history of childhood victimization. It was shown that childhood victimization did not predict drug misuse, but attachment did.…”
Section: Drug Misuse Attachment and Gendermentioning
confidence: 99%
See 2 more Smart Citations